EKSISTENSI PERADILAN TATA USAHA NEGARA DALAM PENYELENGGARAAN PEMERINTAHAN - Aspani, Budi (Solusi, 2019)
Legal protection of citizens for acts committed by the authorities can be done through 3 (three) bodies, namely the State Administration Agency, through administrative efforts, the State Administrative Court, based on Undag - Law Number 5 of 1986, General Judiciary, through Article 1365 of the Civil Code. In an effort to approach the main problem in this study, the authors use the type of library research that is descriptive analysis, namely by conducting research on library materials, then carried out an analysis by referring to the laws and regulations in the fields related to the problem under study. After discussing the existing problems, it can be concluded that the authority or competence of the State Administrative Court Judge is to examine, decide upon and resolve the State Administration dispute between civil persons or legal entities as a result of the issuance of a State Administration Decree. The State Administration Decree issued by the State Administration Agency / Officer can be denied by submitting Administrative Efforts consisting of Administrative Objections and Appeals. Against Decisions Administrative efforts in the form of administrative objections and appeals can be filed with the State Administrative Court within a grace period of 90 (ninety) days from the date of receipt or announcement of the Decree of the State Administration Agency / Officer.